SEJARAH DAN PERKEMBANGAN OBOE SERTA IMPLEMENTASINYA TERHADAP TEKNIK PERMAINAN - imal yakin (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
Oboe instrument first time created by Jean Hotteterre and Michel Philidor in the year 1660, and  first time used in writing in music partitur in the year 1671 in activity opera "Pomone" Robert Cambert of masterpiece in Paris. Oboe Instrument experience of the growth differentiating the instrument with the shwam instrument. One of its growth form bell and there are baluster of instrument tabletop, while equalizing the individuality from that instrument using mouthpiece of consisted  three separate shares that is, staple, piroutte, and reed. Oboe growth of instrument at present day that goes on during 90 year can be assumed two period, and three ' key'. During century of XIX of instrument of oboe a lot of experiencing of growth in its effort improve;repair the intonation and water down the finger. The growth with the addition process six ' key'.  Technique play at the oboe majored to be divided by into two form, 1) Body position and way of holding instrument, this matter is more addressed to respiration technique for example: shoulder exhalation, chest exhalation, stomach exhalation, and diaphragm exhalation 2) recognition Ambasir with the especial target hit is the function of ambasir and forming ambasir.